The effect of a roundabout corridor’s design on selecting the optimal crosswalk location: a multi-objective impact analysis - Fernandes, Paulo J. (2018)
Crosswalks located at mid-block segment between roundabouts can provide a good balance among delay, carbon dioxide (CO2) emissions and relative difference between vehicles and pedestrians speed. However, when considering local pollutant criteria, the optimal crosswalk location may be different to that obtained for CO2. This paper described a multi-objective analysis of pedestrian crosswalk locations, with the objectives of minimizing delay, emissions and relative difference between vehicles and pedestrians speed. Accounting for the difference between global (e.g. CO2) and local pollutants (monoxide carbon, nitrogen oxides and hydrocarbons) was one the main considerations of this work. Vehicle activity along with traffic and pedestrian flows data at six roundabout corridors in Portugal, one in Spain and one in the US were collected and extracted. A simulation environment using VISSIM, VSP, and SSAM models was used to evaluate traffic operations along the sites. The Fast Non-Dominated Sorting Genetic Algorithm (NSGA-II) was implemented to further search optimal crosswalk locations. The results yielded improvements to both delay and emissions by using site-optimized crosswalks. The findings also revealed that the spacing between intersections widely influenced the optimal crosswalk location along a mid-block section. If the spacing is low (<100 m), the crosswalk location will be approximately in 20%-30% of the spacing length. For spacing values between 140 and 200 m, crosswalks would be located at the midway position. When a specific pollutant criterion was considered, no significant differences were observed among optimal crosswalk data sets.